Encouraging job crafting in the workplace for newcomers: A two-year multi-wave study - Jeong, Seoyeong; Kim, Sunyoung; Seol, Jeong Hoon; Lim, Myongki; Sohn, Young Woo (Frontiers in Psychology, 2022)
It is important to identify the antecedents of newcomers’ job crafting as it assists with their adjustment in the workplace. Based on the job crafting model (Wrzesniewski & Dutton, 2001), this study made use of transformational leadership and newcomers’ calling as organizational and personal resources that predict job crafting. This study hypothesized that transformational leadership would have a significant indirect relationship with newcomers’ job crafting after two years through their occupational self-efficacy and that their calling would moderate this mediational path. A multi-wave approach was employed wherein data from 280 new employees were collected three times during the first two years of their careers. The survey was completed by 150 participants. The results illustrated that transformational leadership was positively related to newcomers’ job crafting after two years of entry through their occupational self-efficacy. Additionally, newcomers’ calling moderated the mediating effect of occupational self-efficacy between transformational leadership and job crafting. The theoretical and practical implications of this study are discussed.